Design of Gas Oven Temperature Control System Using PID Method - Wisnel; Eri Wirdianto; Prima Fithri (Journal of Creative Power and Ambition (JCPA), 2026)
This paper presents the design and implementation of an automatic oven for baking marble sponge cake using a PID-based temperature control system. The proposed system regulates oven temperature and air circulation to achieve stable and uniform baking conditions. Temperature control is implemented using a PID algorithm based on feedback from a K-type thermocouple sensor, while air circulation is controlled by a DC blower motor driven through PWM and a BTS7960 driver. The overall system is controlled by an Arduino Uno R3 microcontroller. PID parameters were determined using the Ziegler–Nichols reaction curve method, resulting in ???????? = 16.4, ???????? = 90 s, and ???????? = 22.5 s. Experimental results show that the oven was able to reach and maintain a setpoint temperature of 175 ∘C with acceptable stability during a 28-min baking process. Therefore, the developed system can be considered effective for automatic marble sponge cake baking requiring stable and controlled thermal conditions.